Reduction of Antimicrobial Resistance and Limiting Use of Antibiotics by the Application of De-escalation and Streamlining: A Review Update - Saha, Ritu; Uddin, Bhuiyan Mohammad Mahtab (Journal of National Institute of Neurosciences Bangladesh, 2020)
De-escalation is a critical component that lies at the center of antimicrobial stewardship programs. It is a clinically effective concept in reducing infection with drug resistant isolates. Although there is significant and serious shortfalls like establishment of the real impact of de-escalation on antimicrobial resistance development; it is now well demonstrated that there is no harm for patients, whether it genuinely improve clinical outcomes. Further studies are needed to establish the most effective tools to implement de-escalation, particularly in terms of providing clear guidelines to clinicians to enable them to be confident in applying this maneuver in our country. It is interesting that this concept of de-escalation is now being explored in different types of infection. Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 140-142